Closing the gap in paediatric ventricular assist device therapy with the Berlin Heart EXCOR® 15-ml pump† - De Rita, Fabrizio; Goldwasser, Ranny (Interactive cardiovascular and thoracic surgery, 2017)
OBJECTIVES: The Berlin Heart EXCORVR (EXCOR) paediatric ventricular assist device is used worldwide for mechanical support of infants and small children with end-stage heart failure. A clinically important gap between the smallest EXCOR blood pump (10 ml) and the next larger size (25 ml) limited the choice of pump size in patients with a body surface area (BSA) between 0.33 and 0.5 m2. We present the ﬁrst clinical experience from the early product surveillance (EPS) of the new EXCOR 15-ml blood pump. METHODS: After CE and U.S. Food and Drug Administration approval in January 2013, 20 patients with a mean age of 1.6 years (range 0.5-3.5 years) and a mean BSA of 0.45 m2 (range 0.33-0.59 m2) were enrolled in the EPS. The main diagnosis was idiopathic cardiomyopathy in 13 patients; the majority (n = 16) of children were in INTERMACS level 1 or 2. Data from high-volume paediatric transplant centres were collected prospectively for a deﬁned follow-up period of 60 days after device implantation.RESULTS: Mean time on the EXCOR 15-ml blood pump was 43 days; the survival rate was 100% at the end of the EPS period. Seven patients underwent a heart transplant from the device; 2 children were weaned; and 11 patients remained on support. Infection of cannula exit sites occurred in 3 patients. Two patients had minor thromboembolic strokes but made a complete neurological recovery.CONCLUSIONS: The new EXCOR 15-ml blood pump demonstrated optimal ventricular assist device support of children with a BSA of 0.33-0.5 m2.